Pengembangan modul pembelajaran matematika berbasis permainan treasure hunt untuk pembelajaran numerasi pada materi pengolahan data kelas IV sekolah dasar - Dimas Sapril Saputra; Karsono Karsono (Didaktika Dwija Indria, 2025)
This study aims to develop a Treasure Hunt game-based mathematics learning module for numeracy learning in data processing material for fourth grade elementary school students. This study employs the Research and Development (R&D) method using the ADDIE development model, which consists of the analysis stage, the design stage, the development stage, the implementation stage, and the evaluation stage. The developed module was validated by 2 subject matter experts, 2 media experts, 2 language experts, and 10 education practitioners. The validation results showed that the module received a score of 94.9% from media experts, 90.5% from subject matter experts, 93.1% from language experts, and 93.5% from education practitioners, all of which fall into the highly valid category. Additionally, the results of the practicality test through a limited trial by fourth-grade students at SD Negeri Gading Surakarta showed a percentage of 90.8%, categorizing it as highly practical. Based on these results, the module is deemed highly valid and highly practical, making it suitable for use as supplementary teaching material in numeracy education at elementary schools.